The role of milk-derived exosomes in the treatment of diseases - Rashidi, Mehdi; Bijari, Salar; Khazaei, Amir Hossein; Shojaei-Ghahrizjani, Fereshteh; Rezakhani, Leila (Frontiers in Genetics, 2022)
Exosomes (EXOs) are natural nanoparticles of endosome origin that are secreted by a variety of cells in the body. Exosomes have been found in bio-fluids such as urine, saliva, amniotic fluid, and ascites, among others. Milk is the only commercially available biological liquid containing EXOs. Proof that exosomes are essential for cell-to-cell communication is increasingly being reported. Studies have shown that they migrate from the cell of origin to various bioactive substances, including membrane receptors, proteins, mRNAs, microRNAs, and organelles, or they can stimulate target cells directly through interactions with receptors. Because of the presence of specific proteins, lipids, and RNAs, exosomes act in physiological and pathological conditions in vivo. Other salient features of EXOs include their long half-life in the body, no tumorigenesis, low immune response, good biocompatibility, ability to target cells through their surface biomarkers, and capacity to carry macromolecules. EXOs have been introduced to the scientific community as important, efficient, and attractive nanoparticles. They can be extracted from different sources and have the same characteristics as their parents. EXOs present in milk can be separated by size exclusion chromatography, density gradient centrifugation, or (ultra) centrifugation; however, the complex composition of milk that includes casein micelles and milk fat globules makes it necessary to take additional issues into consideration when employing the mentioned techniques with milk. As a rich source of EXOs, milk has unique properties that, in addition to its role as a carrier, promotes its use in treating diseases such as digestive problems, skin ulcers, and cancer, Moreover, EXOs derived from camel milk are reported to reduce the risk of oxidative stress and cancer. Milk-derived exosomes (MDEs) from yak milk improves gastrointestinal tract (GIT) development under hypoxic conditions. Furthermore, yak-MDEs have been suggested to be the best treatment for intestinal epithelial cells (IEC-6 cell line). Because of their availability as well as the non-invasiveness and cost-effectiveness of their preparation, isolates from mammals milk can be excellent resources for studies related to EXOs. These features also make it possible to exploit MDEs in clinical trials. The current study aimed to investigate the therapeutic applications of EXOs isolated from various milk sources.